FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN - Indry Laraswati; Thio Lie Sha (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research aims at how the effect of liquidity, profitability, firm sze, firm growth on property, real estate, and building construction industry listed on the Indonesia Stock Exchange during 2015-2019. Sample was selected using purposive sampling method and the valid data was 15 companies. Data processing techniques using panel data regression analysis what helped by Eviews program (Econometric Views) for Windows vers. 10.0 and Microsoft Excel 2013. The results of this study indicate that independent liquidity, profitability, and firm growth have a significant influence on dividend policy, and firm sizehave no significant effect on dividend policy. The implication of this study is the need to increase the company management to increase firm.